2022
DOI: 10.1128/spectrum.01234-22
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Symbiotic Digestion of Lignocellulose in the Digestive System of a Fungus-Growing Termite

Abstract: Fungus-farming termites have a mutualist association with fungi of the genus Termitomyces and gut microbiota to support the nearly complete decomposition of lignocellulose to gain access to nutrients. This elaborate strategy of plant biomass digestion makes them ecologically successful dominant decomposers in (sub)tropical Old World ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…More importantly our results showed that SnakeMAGs was able to recover MAGs encompassing the major bacterial phyla found in termite guts, 32 , 33 and that some of these phyla were not recovered by ATLAS. Indeed, taxa belonging to Verrucomicrobiota, 34 Planctomycetota, 33 , 35 Synergistota, 36 Elusimicrobiota 37 and Acidobacteriota 38 , 39 have been repeatedly found in the gut of various termite species. As such, they would represent relevant targets for genome-centric analyses of the termite gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly our results showed that SnakeMAGs was able to recover MAGs encompassing the major bacterial phyla found in termite guts, 32 , 33 and that some of these phyla were not recovered by ATLAS. Indeed, taxa belonging to Verrucomicrobiota, 34 Planctomycetota, 33 , 35 Synergistota, 36 Elusimicrobiota 37 and Acidobacteriota 38 , 39 have been repeatedly found in the gut of various termite species. As such, they would represent relevant targets for genome-centric analyses of the termite gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Faith’s phylogenetic diversity ( 81 ) was calculated to determine phylogenetic diversity in the microbial communities, and Pielou’s evenness ( 82 ) was used for community evenness evaluation. For beta diversity, Jaccard similarity ( 83 ), Bray-Curtis dissimilarity ( 84 ), and weighted and unweighted UniFrac distances ( 85 ) were calculated,and were visualized by PCoA plots using ggplot2 ( 86 ).…”
Section: Methodsmentioning
confidence: 99%
“…To date, the proposed mechanisms for retaining Termitomyces monocultures and suppressing the growth of pathogenic fungi within termites’ nests include social behavior, favorable nest microclimate condition maintenance, chemical secretions such as antimicrobial peptides, and the exploitation of symbiotic bacteria [ 56 , 60 ]. Apart from termites and fungi , diverse bacteria (such as Bacteroidetes, Proteobacteria, Firmicutes, Spirochaetes, Synergistota, and Actinobacteria) have been described in the guts and fungus combs of termites [ 60 , 61 ]. It is well documented that the symbiotic bacteria of termites have crucial functions in carbohydrate metabolism, cello-oligomer or lignin degradation, fungal cell wall degradation, atmospheric nitrogen fixation, reductive acetogenesis, and production of antimicrobial metabolites [ 7 , 55 , 56 , 60 , 61 ].…”
Section: Typical Examples Of Mutualisms Regarding Insects With Symbio...mentioning
confidence: 99%
“…Apart from termites and fungi , diverse bacteria (such as Bacteroidetes, Proteobacteria, Firmicutes, Spirochaetes, Synergistota, and Actinobacteria) have been described in the guts and fungus combs of termites [ 60 , 61 ]. It is well documented that the symbiotic bacteria of termites have crucial functions in carbohydrate metabolism, cello-oligomer or lignin degradation, fungal cell wall degradation, atmospheric nitrogen fixation, reductive acetogenesis, and production of antimicrobial metabolites [ 7 , 55 , 56 , 60 , 61 ]. The multipartite symbiotic system (fungus–termite–bacterium) in fungus-growing termite nests is sophisticated.…”
Section: Typical Examples Of Mutualisms Regarding Insects With Symbio...mentioning
confidence: 99%